PENATAAN STRUKTUR ORGANISASI PADA SEKRETARIAT DAERAH KABUPATEN MINAHASA TENGGARA - LANGINGI, FEBRIAN; POSUMAH, JOHNNY HANNY; RARES, JOYCE (JURNAL ADMINISTRASI PUBLIK, 2019)
The Organizational Structure of the Regional Secretariat of the Southeast Minahasa Regency hasbeen effective. In other words, the regional secretariat organization of the Southeast Minahasa district isnow able to create or realize the implementation of the main tasks and functions of the area secretariateffectively. The effectiveness of the organizational arrangement of the Southeast Minahasa regionthe secretariat can be demonstrated by several criteria: rationality, according to needs, efficiency, can functionoptimally, can target optimal results, can use the budget appropriately and efficiently, able to anticipate thedevelopment and improvement of tasks/jobs and able to overcome problems or obstacles/obstacles that arisein the implementation of tasks and functions. Based on the conclusions from the results of the study it issuggested that the analysis of organizational needs is always done periodically and continuously so that thefuture of the organization of the Regional Secretariat of the Southeast Minahasa Regency will be moreeffective in carrying out its duties and functions as mandated by applicable law.Keywords: Effectiveness, Organizational Structuring